User modelling: A global perspective - Wilson, Tom (Anales de Documentación, 1999)
It is now widely recognized that the design of computer-based information systems is more than a technical or technological problem. Participative design technologies such asthat developed by Mumford [1] and the use of Soft Systems methodology [2][3], are now widely recognized as necessary to ensure that systems devised for organizational use fitthe needs of departmental users. Thus, in the financial services sector one might expect to find a majority of departmental staff on a development team rather than a majority of systems analysts and programmers.However, there is still something of a gap between the recognition of departmental or organizational needs and their satisfaction in systems terms and the recognition of theperspective of the individual information user. This paper seeks to address that issue by proposing a wider perspective of the user than that commonly adopted in modelling userbehaviour